MiA: Designing and prototyping a maternity assistant system - Arce-Murillo, María Fernanda (2020)
In the framework of the current market, where people are constantly searching for tools to facilitate their lives, we developed a system of intelligent objects to help in motherhood tasks. To start the project, subjects with the “recent parent-hood” characteristic were studied to determine the most outstanding necessities and duties that accompany this circumstance. After acknowledging these necessities, the problems were synthesized: efficiently preparing baby bottles, and watching after the infant for a brief period. Following these findings, the designing concept was stated; based on it, the solution sketches were drawn, and evaluated with the necessities determined, until the one that met the criteria the most was found. Then, it was high fidelity-prototyped via 3D printing and finally tested with real users to validate the final product.